Energy Balance Analysis to Assess Efficiency Improvements with Low Heat Rejection Concepts Applied to Low Temperature Combustion. Issue 4 (3rd April 2017) - Penny, Michael A.; Jacobs, Timothy J.
ABSTRACT: Simultaneously decreasing diesel engine emissions while increasing engine efficiency can be a challenge. The results of recent computational and experimental studies, however, have indicated that emissions can be decreased while simultaneously increasing efficiency through the application of low heat rejection (LHR) techniques to low temperature combustion (LTC). One such recent experimental study showed simultaneous decreases in nitrogen oxides and smoke from a light-duty, multi-cylinder diesel engine and serves as motivation to the present study. The major conclusion from that study is that combining LHR with LTC substantially increases LTC brake fuel conversion efficiency through increases in both combustion efficiency (i.e., decreased hydrocarbon and carbon monoxide emissions) and brake thermal efficiency. LTC is realized through high levels of exhaust gas recirculation and retarded injection timings while different degrees of LHR are achieved by means of higher coolant temperatures, which should serve to decrease the temperature gradients across the cylinder walls. It is clear that the increase in brake thermal efficiency is the significant contributor to the increase in brake fuel conversion efficiency; it is not clear, however, what necessarily drove the increase in brake thermal efficiency. Seeking clarity to this issue is the motivation of the current study. This study explores in more detail the increase in brake thermal efficiency in an attempt to understand what influence LHR has on LTC efficiency improvements. This study is satisfied through analysis of the quantification of various efficiencies (i.e., net indicated thermal, net indicated fuel conversion, and brake fuel conversion efficiencies) and the many energy transfer terms (i.e., energy balance analysis). The energy balance analysis specifically reveals insight in how energy transferred through the coolant compares to those changes observed with power and exhaust energy. Specifically, the energy balance confirms important insights offered by the efficiency analysis as related to the operation of LTC at high engine coolant temperature compared to low coolant temperature. It is concluded that the chief reason for efficiency improvement with LTC at high engine coolant temperature (i.e., the LHR condition), compared to low engine coolant temperature, is improved combustion phasing; combustion efficiency is also improved. The results suggest that LTC efficiency improvements can be realized with higher operating engine coolant temperatures under light-load engine conditions.